Clouding the Judgment of Domestic Violence Law: Victim Blaming by Institutional Stakeholders in Cambodia - Brickell, Katherine (J Interpers Violence, 2015)
This article examines victims’ purported complicity in the judicial failures of domestic violence law to protect them in Cambodia. It is based on 3 years (2012-2014) of research in Siem Reap and Pursat Provinces on the everyday politics of the 2005 “Law on the Prevention of Domestic Violence and the Protection of the Victims” (DV Law). The project questioned why investments in DV Law are faltering and took a multi-stakeholder approach to do so. In addition to 40 interviews with female domestic violence victims, the research included 50 interviews with legal and health professionals, NGO workers, low- and high-ranking police officers, religious figures, and local government authority leaders who each have an occupational investment in the implementation and enforcement of DV Law. Forming the backbone of the article, the findings from this latter sample reveal how women are construed not only as barriers “clouding the judgment of law” but also as actors denying the agency of institutional stakeholders (and law itself) to bring perpetrators to account. The findings suggest that DV Law has the potential to entrench, rather than diminish, an environment of victim blaming. In turn, the article signals the importance of research on, and better professional support of, intermediaries who (discursively) administrate the relationship between DV Law and the victims/citizens it seeks to protect.